SURVIVAL MODELS AND RISK FACTORS OF BREAST FEEDING IN URBAN AND RURAL AREAS OF TAKESTAN-INTRODUCING SURVIVAL ANALYSIS - M.R. Eshraghian; H.R Khoram Khorshid (Tehran University of Medical Sciences, 1999)
In this paper, by using the Survival models, survival functions for the time from birth to the event of using formula (i.e. the time that baby in fed by breast milk) in urban and rural areas of Takestan (Iran, Winter 1998) are reported. Later the relation between the mentioned time and some factors are also discussed. The Kaplan-Meire Method and Cox Regression are used in this paper as well. 480 babies from urban areas and 720 from rural areas were chosen to be included in this research. It was shown that 7.7% of babies in urban and 6.5% in rural areas were fed by formula. The mean time of feeding by breast milk, before using formula, in urban and rural areas was 2.5 and 2 months, respectively. It was also shown that the survival functions of time that a baby fed by breast milk was not significantly different in urban and rural areas (P=0.50). The survival functions of the mentioned time in different sexes for both urban (P = 0.62) and rural (P = 0.62) areas were not significantly different. It was also shown that in urban areas the discussed survival functions were significantly different. In different mother's age groups (P = 0.03) and in groups of mothers with and without a job (P = 0.0001). Cox Regression showed that the hazard of a baby, belonged to a mother whit a job, being fed by formula was 6.31 times of a baby, belonged to a mother without a job. It also showed that the babies of older mothers were more at risk of being fed by formula. The mean time of using breast milk for mothers with and without a job was 17 and 23 months, respectively.